2009
DOI: 10.1007/s10157-009-0161-y
|View full text |Cite
|
Sign up to set email alerts
|

Albumin thiol oxidation and serum protein carbonyl formation are progressively enhanced with advancing stages of chronic kidney disease

Abstract: Background Oxidative stress is enhanced in advanced chronic kidney disease (CKD) patients and recognized as a main contributor to cardiovascular disease. Carbonyl stress is also known to be enhanced in advanced CKD; however the precise relationship between oxidative stress and carbonyl stress is not clear. The aim of this study was to investigate potential relationships between oxidative stress, carbonyl stress, and renal function among predialysis patients with CKD. Methods A total of 32 predialysis CKD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 40 publications
2
48
0
3
Order By: Relevance
“…Therefore, the increase in renal damage induces a rise in oxidative stress, thus increasing the quantity of these proatherogenic thiols linked to LDL. This is consistent with recent findings which have described that the plasma levels of the reduced form of albumin (albumin-Cys 34 -SH) decreased progressively with a decrease in renal function of CKD patients, leading to an increase of the oxidized form of protein (albumin-Cys 34 -S-S-X) [35]. …”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the increase in renal damage induces a rise in oxidative stress, thus increasing the quantity of these proatherogenic thiols linked to LDL. This is consistent with recent findings which have described that the plasma levels of the reduced form of albumin (albumin-Cys 34 -SH) decreased progressively with a decrease in renal function of CKD patients, leading to an increase of the oxidized form of protein (albumin-Cys 34 -S-S-X) [35]. …”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have supported our finding indicating that the uremic state is associated with low concentrations of glutathione and reduced thiols (SH), which continue to decrease with the progression of kidney failure in dialysis patients (16). In addition, Matsuyama et al showed that the redox state of Cys-34 (free thiol group) of human serum albumin correlated with the level of renal dysfunction in predialysis chronic kidney disease patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…HPLC system for measuring the albumin redox state Measurement of the albumin redox state was performed by a previously-reported HPLC method [Matsuyama et al 2009a;Matsuyama 2009b]. Briefly, the HPLC system consisted of an AS-8010 auto-sampler (using an injection volume of 2 µL of sample) and a CCPM double-plunger pump in conjunction with an SC-8020 system controller (all from Tosoh, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%